IMPACT OF OCTREOTIDE ON LUNG RECOVERY IN ACUTE EXPERIMENTAL CAERULEIN-INDUCED PANCREATITIS - Vastyanov, R.S.; Stoyanov, O.M.; Tertyshnyi, S.V.; Babienko, V.V.; Hruzevskiy, O.A.; Talalayev, K.O.; Vastianov, M.R. (World of Medicine and Biology, 2025)
The purpose of the study was to provide the pathophysiological explanation of octreotide therapeutic effect on lung recovery in acute experimental pancreatitis. Experimental studies were performed on the model of caerulein-induced acute pancreatitis on Wistar rats which were injected with Octreotide. NaCl solution was used as a reference drug. The expression of lipoperoxidation and antioxidant defense together with pathomorphological changes in pancreas and lungs were determined during the 48 hrs of the trial. The inducible NO synthase activity, the content of tumor necrosis factor, interleukin-1 and intercellular adhesion molecule were determined in blood serum. The data obtained confirm the lipoperoxidation products accumulation, the antioxidant enzymes activity inhibition and pathomorphological changes in pancreatic and lungs cells of rats with caerulein-induced acute experimental pancreatitis. The inducible NO-synthase activation, the proinflammatory cytokines and intercellular adhesion molecules content increase is recorded in blood serum of rats with caerulein-induced acute experimental pancreatitis. The Octreotide injection causes the pneumoprotective efficacy which mechanisms of implementation involve its antiinflammatory, antioxidant and antihypoxic effects. The authors supposed the data obtained are the experimental evidence of Octreotide clinical efficacy testing reasonability to prevent lung damage in acute inflammatory lesions of the pancreas.